AW-NI-2: A HIGH-FIBRE DIET ATTENUATES HYPERTENSION BY IMPROVING GUT BARRIER INTEGRITY VIA SCFA-RECEPTOR SIGNALLING. (January 2023) - Muralitharan, Rikeish R; Dinakis, Evany; Xie, Liang; Jama, Hamdi; Nakai, Michael; Paterson, Madeleine; Johnson, Chad; Salimova, Ekaterina; Bitto, Natalie; Liaskos, Maria Kaparakis; Donnell, Joanne A O; Mackay, Charles R; et al.
Abstract : Objective: The gut microbiome has been recently discovered to play a role in blood pressure (BP) regulation. Short-chain fatty acids (SCFAs), produced from the fermentation of fibre by the gut microbiota, are protective in experimental hypertension models. However, whether the protective effects of fibre are dependent on SCFA-receptor (GPR41, GPR43) signalling is not known. This is relevant as hypertensive patients have a deficiency in GPR43. We aimed to determine whether SCFA-receptor signalling is relevant in hypertension, whether the protective effects of a high-fibre diet depend on SCFA-receptor signalling, and the underlying mechanisms involved. Design and Methods: We induced hypertension using angiotensin II (Ang-II, 0.5 mg/kg/day) in wild-type and the novel GPR41/43 double knockout (DKO) male mice (n = 9–15). We fed wild-type and DKO mice high-fibre (n = 6–7) or standard diets (n = 9–15). Another cohort received TLR4 antagonist treatment (n = 6–7). We measured BP by tail-cuff, performed Mason trichrome staining for fibrosis in the heart and kidney, and immunofluorescence staining for zonulin-1, a key tight junction protein to determine gut permeability, in the colon. Results: When fed a standard diet and challenged with Ang-II, DKO mice had significantly higher BP, mortality, cardiorenal hypertrophy and fibrosis, and lower zonulin-1 in the colon compared to wild-type mice (all P < 0.05). A high-fibre diet partially protected DKO mice, resulting in significantly lower BP, mortality, cardiorenal hypertrophy, and fibrosis (all P < 0.05). Mice fed high-fibre had significantly higher zonulin-1 expression in the colon (P < 0.05), meaning that a high-fibre diet improved gut barrier integrity. This suggests that the protective effects of high-fibre partially depend on GPR41/GPR43 signalling. Hypertensive wild-type and DKO mice had significantly higher plasma TLR4 activation suggesting its ligand, microbial lipopolysaccharides (LPS), is in the circulation (P < 0.05). TLR4 activation leads to inflammation and subsequent tissue damage that could be responsible for the phenotype observed. Thus, we treated hypertensive DKO and wild-type mice with a TLR4 antagonist (i.p., injection of 50 μg/kg/body weight twice weekly). The severity of DKO hypertensive mice was rescued to the level of WT when treated with the TLR4 antagonist - no difference from wild-type mice in terms of BP, mortality, organ weights, and fibrosis. Conclusions: We revealed for the first time that a high-fibre diet attenuates hypertension by improving gut barrier integrity via the SCFA-receptors GPR41 and GPR43. This leads to lower translocation of harmful microbial substances such as LPS from the gut and activation of its receptor TLR4 to induce inflammatory responses that promote hypertension.